Ministry Of Trade And Industry Decree No. 32 Of The Year 2010 On Enforcing Production In Compliance With The Standard Specifications = وزارة التجارة والصناعة قرار رقم 32 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.